Bio-semantics, ecology and content ascription (2011)
Advocates of bio-semantics propose that the content of representations be fixed with reference to their biological function. A legitimate plurality of etiological functions for a given representation, however, stands in the way of fixing content. Attempts to overcome this problem for content ascription with a counterfactual argument have been accused of misusing the selection for/selection of distinction. I reconstruct the counterfactual argument in the context of the constraints on evolutionary design that underlie an ecological theory of selection pressures. I then argue that these constraints assign a modest role to etiological function in a method for content ascription. But it requires abandoning the claim that a priori thinking in terms of etiological function will solve content ascription; in particular, it cannot replace cognitive theory and experimentation. As behavioural ecologists have warned, biological functions should not be too quickly translated into proximate, in particular perceptual, mechanisms.